'Don't give us an assignment where we have to use spinach!': food choice and discourse in home and consumer studies. (29th May 2015) - Bohm, Ingela; Lindblom, Cecilia; Åbacka, Gun; Hörnell, Agneta
Abstract: The aim of the study was to describe classroom Discourses about vegetables during the planning, cooking, eating and evaluation of meals in the Swedish school subject Home and Consumer Studies. Fifty‐nine students and five teachers were recruited from five northern Swedish villages and towns, and then observed, recorded and in some cases video‐taped during lessons that took place between 2010 and 2012. Based on 56 instances of talk about vegetables, four Discourses were identified and related to the three aspects of Belasco's culinary triangle of contradictions: identity, responsibility and convenience. The results indicated that the identity‐based sensory and cultural Discourses sometimes clashed with the more responsibility‐oriented health and evaluation Discourses. The health Discourse was only used when there was an element of evaluation, with assignments connected to grades. In all other cases, the sensory and cultural Discourses guided vegetable use. Sometimes different sensory or cultural assumptions could clash with each other, for example when the teacher insisted on the use of a specific recipe regardless of a student's taste preferences. Since these preferences did not always harmonize with curricular demands for responsibility, there might be a risk of basing grades on aspects of students' identity. Alternatively, students might feel constrained to argue against their own identity in order to be favourably evaluated. Then again, if teachers always bow to student tastes, this limits their chances of learning about food and physical health. Viewing the dilemma through the lens of the culinary triangle of contradictions may help teachers and researchers develop teaching methods that take all aspects of food choice into account.